Prevalence and characteristics of portopulmonary hypertension in cirrhotic patients who underwent both hepatic vein and pulmonary artery catheterization. Issue 11 (1st September 2020) - Atsukawa, Masanori; Tsubota, Akihito; Hatano, Masaru; Kondo, Chisa; Shioda, Kaori; Ohno, Hiroki; Kawano, Tadamichi; Hayama, Korenobu; Arai, Taeang; Nakagawa‐Iwashita, Ai; Itokawa, Norio; Kaneko, Keiko; et al.
Aim: Portopulmonary hypertension (PoPH) is a well‐known complication of liver cirrhosis. The aim of this study was to clarify the pulmonary hemodynamics and the prevalence and characteristics of PoPH in patients with portal hypertension. Methods: The subjects were 335 patients with portal hypertension diagnosed by hepatic vein pressure gradient (HVPG). Among them, 186 patients received measurements of pulmonary artery pressure (PAP), pulmonary artery wedge pressure (PAWP) and pulmonary vascular resistance (PVR). PoPH was diagnosed by PAP >20 mmHg, PVR ≥3 Wood units (WU) and PAWP ≤15 mmHg. Results: The Child–Pugh classification was class A in 53, B in 92 and C in 41 patients. Median (range) values of HVPG, PAP, PVR and PAWP were 18.4 (5.5–39.0) mmHg, 12.9 (6.6–40.8) mmHg, 0.8 (0.1–4.5) WU and 7.5 (2.2–15.4) mmHg, respectively. Of six patients with PAP >20 mmHg, four had autoimmune hepatitis or primary biliary cholangitis, with the prevalence being significantly higher than that in patients with PAP ≤20 mmHg. Meanwhile, no significant difference was noted in the hepatic functional reserve or HVPG between patients with PAP >20 mmHg and ≤20 mmHg. Only two patients met the diagnostic criteria of PoPH and both patients were Child–Pugh B. The Child–Pugh score and HVPG were not associated with PoPH. Conclusions: Our study demonstrated that only two patients were complicated by PoPH. High PAP values were noted in patients with primary biliary cholangitis or autoimmune hepatitis. However, the presence of PoPH and high PAP were not associated with the degree of hepatic functional reserve or HVPG.